Systematic Review and Meta-analysis of Linkage to HIV Care Interventions in the United States, Canada, and Ukraine (2010–2021). - Levison, Julie H.; Del Cueto, Paola; Mendoza, Jaime Vladimir; Ashour, Dina; Lydston, Melis; Freedberg, Kenneth A.; Shebl, Fatma M. (AIDS & Behavior, 2023)
We conducted a systematic review and meta-analysis of interventions targeting linkage to HIV care in the US, Canada, and Europe. We searched six databases (PubMed, Embase, Cochrane Library, Web of Science and CINAHL). Inclusion criteria were English language studies in adults in the US, Canada, or Europe, published January 1, 2010 to January 1, 2021. We synthesized interventions by type and linkage to care outcome. The outcome was cumulative incidence of 3-month linkage. We estimated cumulative incidence ratios of linkage with 95% confidence intervals (CIs). We screened 945 studies; 13 met selection criteria (n = 1 from Canada, n = 1 from Ukraine, n = 11 from the US) and were included after full text review (total 37,549 individuals). The cumulative incidence of 3-month linkage in the intervention group was 0.82 (95% CI 0.68–0.94) and control group 0.71 (95% CI 0.50–0.90); cIR of linkage for intervention versus control was 1.30 (95% CI 1.13, 1.49). Interventions to improve linkage to care after HIV diagnosis warrant further attention.